Bubble growth during subcooled nucleate boiling on a vertical heater: A mechanistic attempt to evaluate the role of surface characteristics on microlayer evaporation. (5th May 2019) - Sarker, D.; Ding, W.; Hampel, U.
Highlights: An improved bubble growth model is formulated. The model is validated against the high resolution experimental results. Role of heater surface characteristics on the bubble growth (Ceff ) is derived. The values of Ceff are found lower for the low-wetting surfaces. Ceff is the lowest at the Sq of around 0.12 μm for the low-wetting surfaces. Abstract: For the modelling of nucleate boiling heat transfer, the bubble growth dynamics is of key importance. The study reported in this paper focuses on a qualitative assessment of the role of heater surface parameters on the bubble growth and the effective microlayer thickness constant, C eff . The latter is part of a recently derived improved bubble growth model, which we utilize in our analysis along with high-resolution experimental data of the steam bubble growth. The bubble growth model is formulated considering the evaporation of microlayer beneath the bubble, heat diffusion at the bubble surface and condensation at the bubble cap. We found that the values of C eff are lower and the growth rates of bubble prior to departure are greater at the root mean square roughness of around Sq  = 0.12 μm for low-wetting surfaces. For well-wetting surfaces Ceff and the bubble growth rates are also found lower and greater, respectively at Sq  = 0.15 μm. Finally, a generalized equation for C eff is proposed which comprises the effects of surface roughness and wettability on the bubble growth. The findings are useful for improving the bubble growth models and in designing the heater surface in future.